Rehabilitating Catherine Dickens: Memory and Authorial Agency in Gaynor Arnold’s Neo-Victorian Biofiction Girl in a Blue Dress - Ford, Kathryne (Australasian Journal of Victorian Studies, 2016)
Critical work exploring Girl in a Blue Dress (2008), Gaynor Arnold’s biofictional account of Charles and Catherine Dickens’ marriage, predominantly focuses on the long-silenced wife’s opportunity to speak at last, as the Catherine Dickens character (re-christened Dorothea Gibson by Arnold) determines to complete her late husband Alfred Gibson’s unfinished final novel. However, the significance of confronting and constructing memory in the novel has garnered surprisingly little critical attention; this absence is particularly remarkable since the novel is typically touted as an autobiography or memoir. My article traces the import of Dorothea’s memories in her quest to construct a narrative of her interaction with Alfred in which she appears as a valid player in her own story, rather than as a “footnote” to her husband’s overarching narrative. Exploring the ontological slippage between history and story, I argue that through its merging of memory and narratorial agency, this fiction simultaneously effaces—and restores—the facts. Thus reconciled to her past, Dorothea can focus on her future, and the confidence she has discovered through productively remembering ultimately inspires her to work on Alfred’s as yet unfinished final novel. A “footnote” no longer, Dorothea thus transitions from confronting the story of her past to constructing the story of her future, as she appropriates Alfred’s authorial voice to claim co-creatorship of an entirely new narrative. In fine Bakhtinian form, she assumes control of words bearing Alfred’s signature; he may have invented the fictions of his life with Dorothea and his final novel, but it is she who (quite literally) has the last word.By positioning the wife as narratorial detective inspecting memories to uncover the truth of her failed marriage, Arnold invites readers to reconsider (with Dorothea) how facts have been twisted into a convenient fiction and imbues Dorothea with the self-assurance to pursue narrative authority. Paradoxically, through extricating the facts from the fiction of her life, Dorothea is inspired to write fiction herself in an attempt to regain her life. Likewise, Arnold also demonstrates the narrator’s prerogative to celebrate the slippage between fact and fiction: she rehabilitates Catherine Dickens by inviting readers to consider the truth of her history through the memorable mode of story.